Combine body mass index and body fat percentage measures to improve the accuracy of obesity screening in young adults. Issue 1 (January 2017) - Hung, Shang-Ping; Chen, Ching-Yu; Guo, Fei-Ran; Chang, Ching-I; Jan, Chyi-Feng
Highlights: We should combine BIA and BMI for screening obesity and overweight in young adults. Young males have the better BMI and BIA correlation than young females. Obesity prevalence among young Asian women would be underestimated by BMI criteria. Summary: Introduction: Obesity screening among young adult groups is meaningful. Body mass index (BMI) is limited to discriminate between fat and lean mass. Asian young adult group tends to have lower BMI and higher body fat percentage (BFP) than other ethnic groups. Accuracy of obesity screening by commonly used BMI criteria is unclear in young Taiwanese population. Material and methods: A total of 894 young adults (447 males and 447 females) aged 20–26 were recruited. BMI, regional fat percentage and BFP determined by bioelectrical impedance analysis (BIA) were measured. BMI cutoff points were based on the criteria adopted by the Ministry of Health and Welfare in Taiwan. Cutoff points of low or high BFP were defined as 24% in men and 31.4% in women. Results: Prevalence of BFP defining obesity was 14.8% in young men and 27.3% in young women. 23.2% of young men and only 8.3% of young women were classified to overweight or obesity categories according to the BMI criteria. Disagreement was noticed mainly among overweight males and normal weight females. 68.7% of BMI defining overweight young men had low BFP; however, 29.7% of young women of BMI defining normal group had high BFP. Up to 69.7% of young women with high BFP would be missed by BMI category only. Conclusion: Disagreement between BMI and BFP was significant among young adults, especially young women. We suggest combining BMI and BIA for obesity and overweight screening in Asian young adults.